Occupational chronic obstructive pulmonary disorder: prevalence and prevention - Minov, Jordan (Informa UK Limited, 2022)
Occupational chronic obstructive pulmonary disorder, i.e. work-related asthma (WRA) and occupational chronic obstructive pulmonary disease (COPD), are the most common occupational lung diseases in the last decades worldwide. As in the case of the other occupational disorders, these diseases may be prevented.